The exact location and its relation to cognitive method (risk-caution) of University students (Journal of the College of Education for Women, 2019)
The present study aimed to identify the exact location and its relation to cognitivemethod (risk_caution) to university students. The sample consisted of (300) students whowere chosen randomly and equally. The study results indicated that students possess aninternal exact location and they also use risk cognitive method. The study also indicated thatthere is a prophesies which is an exact location for others to reach to caution cognitivemethod. Depending on these results, the study recommended to benefit from the results of thestudy variables and from the measurement of the exact location and method of cognitive(risk_caution) to identify male and female students and especially by consulting units atcolleges to steer those with caution cognitive method in adapting to environmental changes,especially at college, through the development of programs to promote effective behavior.